Blockchain technology in e-business value chains - Josepha Witt; Mareike Schoop (Electronic Markets, 2023)
In electronic business (e-business), innovative technologies such as blockchain technology (BCT) have a fundamental impact on activities along the value chain. The perspective of the value chain in the context of blockchain technology has been explored, but contributions are mainly focused on supply chain management and tangible goods. Hence, the e-business domain lacks research, even though many beneficial features for service value chains and the transaction of intangible goods exist. Therefore, the current paper focuses on (1) how and why value chain activities are supported by using BCT and (2) how the stakeholder's responsibilities change for value chain activities that are affected by BCT. A multiple case analysis of four e-business cases, i.e., Theta, OpenBazaar, Presearch, and Crypviser, is conducted. Based on four ideal value chains by Wirtz (2019) (cf. 4C-Net Model), steps that depend on BCT or that are supported by BCT are outlined. By conducting a cross-case analysis, we derive eight blockchain technology propositions that enlarge the existing knowledge base.
Keywords: O31; 620; Blockchain technology; Value chain; e-business; Multiple case study